NEW PROMISING RICE GENOTYPES OF SP87-1-1-2 AND SP73-3-17 ADAPTIVE TO LOWLAND AND MEDIUM LAND - Hasan, Fitri Utami; Sari, Santika; Zubair, Anas; Carsono, Nono (Universitas Muhammadiyah Yogyakarta, 2020)
High yield potential (more than 8 ton ha-1), resistant to pest and disease, adaptive to specific or broad environment and good palatability are among rice traits preferred by farmers and consumers. In order to develop such superior rice, yield testing at different agro-climates for some promising lines bred is necessary. This study aimed to examine selected rice genotypes in two different environments, namely Indramayu (9m asl) and Jatinangor (752m asl) and to obtain environment factors affecting the plant trait variation. The experiment was conducted during dry season with fifteen F5 genotypes, arranged in an augmented design. Based on Least Significant Increase (LSI), genotypes showing better performance than checks were SP87-1-1 on number of productive tillers and total grain weight, SP73-3-1 on panicle length, total grain weight, and weight of 1000 grains. Meanwhile, SP46-4-1 and SP87-4-1 showed better number of filled grains than checks in Indramayu. There was no genotype performing higher number of empty grains than that of the checks. Based on the Principal Component Analysis (PCA), altitude contributed to high variation of plant traits. SP87-1-1 and SP73-3-1 are recommended to be grown in medium and lowland ecosystems because they have high productivity in both environments.